2020
DOI: 10.1111/medu.14420
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating equivalence and non‐inferiority of medical education concepts

Abstract: Context In medical education, there are often several didactic methods for teaching and learning a specific medical skill. For educators, there are often pragmatic reasons to decide for one or another of them, such as costs, infrastructural requirements, time expenditure or qualification of the teacher. However, a central aspect to consider is the learning outcome: Does a new method achieve a similar learning success as an established standard method? To answer this question, we need an appropriate method to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…16 While various factors, such as staff, material, and time spending and faculty train-ing, may affect developing SBL modules, student learning outcomes should be the most important factor to be considered. 17 This study investigated the effectiveness of the proposed remote SBL module for developing skills in periodontal instrumentation compared with the onsite SBL modules. Our findings indicated that the proposed remote SBL module achieved comparable student learning outcomes, although this module offered a less practice opportunity under faculty instruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 While various factors, such as staff, material, and time spending and faculty train-ing, may affect developing SBL modules, student learning outcomes should be the most important factor to be considered. 17 This study investigated the effectiveness of the proposed remote SBL module for developing skills in periodontal instrumentation compared with the onsite SBL modules. Our findings indicated that the proposed remote SBL module achieved comparable student learning outcomes, although this module offered a less practice opportunity under faculty instruction.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous SBL modules have been implemented to teach different skills in dentistry, but no evidence‐based frameworks guiding SBL curriculum development have been suggested in dental education 16 . While various factors, such as staff, material, and time spending and faculty training, may affect developing SBL modules, student learning outcomes should be the most important factor to be considered 17 . This study investigated the effectiveness of the proposed remote SBL module for developing skills in periodontal instrumentation compared with the onsite SBL modules.…”
Section: Discussionmentioning
confidence: 99%
“…We used an equivalency analysis. 19 We assessed equivalence by determining whether the between-group difference and the associated 95% confidence interval (CI) fell entirely within a pre-stablished equivalence margin (Δ). 20,21,22,23 The data from the results of the pre and post-tests were analyzed with Microsoft Excel 365 (Version 1905; Microsoft Office, Redmond, Washington), https://www.socscistatistics.…”
Section: Discussionmentioning
confidence: 99%
“…We used an equivalency analysis. 19 We assessed equivalence by determining whether the between-group difference and the associated 95% confidence interval (CI) fell entirely within a pre-stablished equivalence margin (Δ). 20 , 21 , 22 , 23 …”
Section: Methodsmentioning
confidence: 99%
“…The trial aims to assess whether tele-instructor based BLS training was non-inferior to a conventional training approach ( 28 ). However, due to an increased infection risk in the 2020 COVID-19 pandemic, a control group using the conventional training approach with group sizes of 12 trainees was not possible.…”
Section: Methodsmentioning
confidence: 99%